Dimensions In The Short Story “Jangan Masuk Hutan Itu!” By Ayu Prawitasari: A Critical Discourse Analysis Of Van Dijk’s Model - Diya Ayu Solehah; Tri Wulandari; Ike Sephia As’at Jody; Hanifullah Syukri (UIN Raden Mas Said Surakarta, Indonesia, 2025)
This research aims to uncover the implied meaning in the short story “Jangan Masuk Hutan Itu!” by Ayu Prawitasari, utilizing Van Dijk's critical discourse analysis model, which encompasses three dimensions: text, social cognition, and social context. This research employed a qualitative descriptive method, collecting data through documentation techniques and analyzing it using a critical discourse approach. The results of the analysis show that this short story displays themes of fear, loss, and mystery through the symbolization of the forest as an uncontrollable force of nature. In the text dimension, the short story reveals the helplessness of the main character in facing the mysterious forest threat. In terms of social cognition, this short story is influenced by the author's personal experience, which implicitly raises feminist discourse, in which female characters struggle to face life's dilemmas without relying on others. The social context in the story reflects the modern social reality of women's freedom in making their life choices. This research contributes to enriching the study of critical discourse analysis, particularly in understanding how literary texts engage with social reality and the author's ideology. Penelitian ini bertujuan untuk mengungkapkan makna tersirat dalam cerpen